2009
DOI: 10.1098/rsta.2009.0020
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing behaviour in man-made engineering materials: bioinspired but taking into account their intrinsic character

Abstract: Man-made engineering materials generally demonstrate excellent mechanical properties, which often far exceed those of natural materials. However, all such engineering materials lack the ability of self-healing, i.e. the ability to remove or neutralize microcracks without (much) intentional human interaction. This inability is the unintentional consequence of the damage prevention paradigm underlying all current engineering material optimization strategies. The damage management paradigm observed in nature can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 38 publications
0
67
0
Order By: Relevance
“…Self-healing materials and surfaces [22][23][24]30,53,[56][57] Damage prevention A mechanism to heal voids as they appear is embedded into material (e.g., nucleation of a solute at void points in supersaturated solid solution).…”
Section: Future Directionsmentioning
confidence: 99%
“…Self-healing materials and surfaces [22][23][24]30,53,[56][57] Damage prevention A mechanism to heal voids as they appear is embedded into material (e.g., nucleation of a solute at void points in supersaturated solid solution).…”
Section: Future Directionsmentioning
confidence: 99%
“…The open volume defects at the interfaces was found to be immobilised by the formation of BN and Cu precipitates at the crack opening [33][34][35].…”
Section: Precipitation Reactionsmentioning
confidence: 99%
“…11). Using differential scanning calorimetry and solid state 13 C NMR spectroscopy healing was observed to predominately result from the solid state DA reaction, and this healing was repeatable for multiple damage events. 174 Later reports showed that full recovery of virgin mechanical properties could be achieved for repeated damage events when fracture surfaces were accurately aligned and clamped with 0?35 MPa of pressure during healing.…”
Section: Thermally Reversible Self-healingmentioning
confidence: 99%
“…thermoplastic polymers, thermoset polymers, composites, metals, etc. ), 12,13 the physical phase of the healing additive (solid v. liquid), 14 the external stimuli required to initiate healing event, 15 and the intrinsic or extrinsic nature of the healing. 16 This ambiguity, which is a direct consequence of the multidisciplinary nature of the field, will likely not be resolved here, but given the spirit of autonomic healing, we organise the different self-healing techniques with the mechanism by which the healing occurs.…”
Section: Introductionmentioning
confidence: 99%